Gastric adenomyoma in the stomach body: a case report - Yoon, Kyung Hwa (J Med Case Rep, 2014)
INTRODUCTION: Gastric adenomyoma is a rare benign tumor, known to occur in the antrum or pylorus of the stomach. To the best of our knowledge, this is the first case reported in the literature of a gastric adenomyoma in the stomach body, but not in the antrum. CASE PRESENTATION: We report the case of a 79-year-old Korean woman with a gastric subepithelial lesion in the stomach body. The lesion was observed via endoscopy as a bulging mass in the stomach body with a cystic center. It was confirmed via endoscopic ultrasonography. A laparoscopic wedge resection was performed. A biopsy revealed epithelial and smooth muscle proliferation, and a final diagnosis of gastric adenomyoma was made. CONCLUSION: Gastric adenomyoma can occur in the stomach body and can be treated completely with surgery.